Making Edible Coating Cucumber Skin (Cucumis Sativus L.) with The Addition of Agar Powder to the Shelf Life of Banana Kepok - Deglas, Welly; Martiyanti, M. Anastasia Ari (Program Studi Teknologi Pangan, 2022)
The purpose of this study was to determine the effect of cucumber peel edible coating with the addition of agar powder on the shelf life of kepok bananas and to see weight loss, pH and fruit appearance with cucumber peel edible coating on the ripening of kepok bananas. The research method used was Completely Randomized Design (CRD) with three replications with 150 grams of cucumber peel extract (P1), 300 grams of cucumber peel extract(P2) and500 gram cucumber peel extract(P3)with storage at room temperature with 3 replications.The percentage of banana fruit weight loss decreased along with the treatment of adding the number of cucumber skins in the manufacture of edible coatings,sthe more addition of cucumber peel extract in the manufacture of edible coating, sowill be thicker in coating the fruit andgood barrier against water,tThe brightness level of bananas is caused by the amount of cucumber peel extract added to the edible coating so that the layer becomes thick and the color and brightness of the bananas darken, weight loss and fruit respiration will be hampered as seen in treatment (P3) the addition of 500 grams of cucumber skin has a weight loss the smallest is 3.16%. smore and moreextractCucumber skin which is added to the edible coating layer becomes thicker so that the decrease in pH in bananas tends to be slightly and can slow down the respiration rate of bananas so that the pH value can be maintained.In treatment (P3) the addition of500 grams of cucumber skin in the manufacture of edible coating shows the pH of bananas for 14 days is 5.0.